Resolving the Contradictions in Parenting Roles within Karo Culture and the Church - Tarigan, Yohan Frananta (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
This article explores the contradictions in parenting role principles between Karo culture and the teachings of the Batak Karo Protestant Church (GBKP). Employing a qualitative method with a literature review approach, the research examines gender roles in parenting through the lens of Karo cultural perspectives and GBKP doctrines. The analysis reveals significant differences in the emphasis on gender roles, posing challenges for Christian Karo families in harmonizing parenting practices with both cultural values and religious teachings. The research recommends a pedagogical approach that balances the roles of fathers and mothers to foster harmonious and holistic parenting. Theoretical and practical implications are discussed to develop a more inclusive Christian family education model.